Malaysian tertiary ESL students' writing errors and their implications on English language teaching / Siti Zawani Mehat and Lilliati Ismail - Mehat, Siti Zawani; Ismail, Lilliati (Universiti Teknologi MARA, 2021)
Errors, either in writing or speaking, are common in second language production. Researchers have long been investigating English as Second Language (ESL) learners' errors because they may produce different kinds of errors than native speakers. The purpose of this study was to identify errors made by adult ESL learners and to examine the L1 interference in writing errors. Writing samples were collected from 30 students enrolled in the academic writing class in Universiti Putra Malaysia, and the errors were identified, recorded, and analyzed to determine whether they were intralingual or interlingual ones. The study results showed that most of the errors were in subject-verb agreement and verb tenses, which could be caused by first language (L1) influence. The findings of this study would shed light on the types of errors these ESL learners make and their weaknesses in using the English language. Besides, the findings could support instructors, curricula creators, and textbook writers to create and offer materials that could help learners enhance their command of the English language.